2001
DOI: 10.1080/obs.80.11.1041.1042
|View full text |Cite
|
Sign up to set email alerts
|

Induction of labor in women with previous cesarean section using the double balloon device

Abstract: Background and methods. To evaluate the efficacy and safety of labor induction by the double balloon device in women with previous cesarean section. Induction of labor was carried out in 37 women with previous cesarean section for various indications. All the inductions of labor were performed using the Atad double balloon device (ARD). Results. Cervical ripening (Bishop scores above 5) was achieved in 82.3% of the induced women with subsequent vaginal delivery in 78.6% and repeat cesarean section in 22.3%. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 2 publications
2
12
0
Order By: Relevance
“…in terms of size (105 vs 418 women), with the remaining seven studies enrolling between eight and 50 women. Similar to the present study, three studies reported that cervical ripening with DBC was useful and safe, resulted in a two‐fold increase in the initial Bishop score, with cesarean delivery rates of approximately 40%–50%, and no substantial increased risk of perinatal adverse events …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…in terms of size (105 vs 418 women), with the remaining seven studies enrolling between eight and 50 women. Similar to the present study, three studies reported that cervical ripening with DBC was useful and safe, resulted in a two‐fold increase in the initial Bishop score, with cesarean delivery rates of approximately 40%–50%, and no substantial increased risk of perinatal adverse events …”
Section: Discussionsupporting
confidence: 87%
“…In the present study, only the initial Bishop score at the time of installation and the Bishop score after removal of DBC appeared to be predictive of VBAC. Khotaba et al . showed that increasing initial Bishop score was associated with an increased rate of VBAC.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 summarises the findings from some of the studies [8][9][10][11] including the current study. Most of the studies showed significant improvement in Bishop score after using the device and a favourable cervix was achieved in 75% to 85% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous references to caesarean section appear in ancient Hindu Egyptians, Greecians, Romans and other European folklore 1 . In past 20 years, the rate of C/S has steadily increased from about 5% to more than 20% 25 .…”
Section: Introductionmentioning
confidence: 99%